LITERATUR REVIEW : HUBUNGAN ANTARA GAYA HIDUP DAN STRES DENGAN KEJADIAN HIPERTENSI PADA LANSIA - Ayu Puspita Sari; Feriana Ira Handian; Nining Loura Sari (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Abstract Hypertension is a disease that is not contagious and often occurs in the community. Hypertension can cause other complications such as stroke, heart, kidney, dementia and visual disturbances. It is said to be hypertension if you have a systolic blood pressure >140 mmHg or a diastolic blood pressure >90 mmHg. This study aims to determine lifestyle and stress with the incidence of hypertension in the elderly. Method: The method used in this study is a literature review using a literature review by searching for journals using 3 databases, namely Google Scholar, Pubmed, and Science Direct. Results and analysis: The results of the research from the 17 journals were 52.9% or 9 journals there was a relationship between lifestyle and the incidence of hypertension and 47.1% or 8 journals stated that there was a relationship between stress and the incidence of hypertension in the elderly. Lifestyles that affect hypertension are lack of physical activity, consuming foods that are high in salt, fat, consuming caffeine, smoking and stress. Excessive stress can also cause hypertension. Discussion and Conclusion: Therefore, in order to avoid disease problems or complications, it is recommended for the elderly to always adjust their lifestyle and control stress well. So that the elderly tend not to have high blood pressure or the occurrence of hypertension.